MODERN CHINESE FOR HERITAGE BEGINNERS stories about us. - Liu, Yan.; Ji, Jingjing; Wu, Grace; Liang, Min-Min. ([S.l.] : ROUTLEDGE, 2023)
Modern Chinese for Heritage Beginners aims to serve as a stepping-stone for Chinese heritage language learners' future Chinese learning, inspiring them to reflect on their identities, learn Chinese American history, and embrace their cultural heritage. The book starts with talking about individuals and families and then expands to the Chinese and Asian American communities in the U.S. and eventually to the entire American society, all from the unique perspective of Chinese American students. Taking a macro approach that builds learners' literacy skills on their initial abilities in speaking and listening, each lesson starts with listening and speaking activities and then moves to reading and writing. The content complexity and language difficulty are balanced to present rich content that matches students' critical thinking abilities in a language appropriate for their literacy level. Lively and humorous language makes the book a joy to read. Each lesson has a conversation and an essay to expose students to informal and formal registers. Moreover, authentic tasks are designed to facilitate students' language output, following the three modes of communication promoted by the American Council on Teaching Foreign Languages: interpersonal, interpretive, and presentational. This theme-based Chinese textbook is written for high school and college-level Chinese heritage language learners.
Keywords: Chinese language -- Textbooks for foreign speakers -- English; FOREIGN LANGUAGE STUDY / General; FOREIGN LANGUAGE STUDY / Chinese